KELAYAKAN USAHA TANAMAN MELATI (Jasminum sambac) DI DESA JINGGAH HABANG ULU KECAMATAN KARANG INTAN KABUPATEN BANJAR - Fitriadi, Subhan; Ttriatmoko, Eddy (Fakultas Pertanian UVAYA Banjarmasin, 2021)
The purpose of this research is to know the revenue,the eksplicit cost ,income and, feasibility. This research was conducted in september – Nopember 2020 at village Jinggah Habang , Banjar regency. The Purposive sampling methode used was by observing 23 farmers in village Jingah Habang Ulu who planted Jasminum sambac plant. The Average result of the revenue is Rp. 3.800.762,/farmer., the average Eksplicit cost is Rp.1.009.120/farmer, and Average income Rp. 1.505.248/farmer and feasibility 1,66 From this result of development of farming Jasminum sambac flant.We believe that it has good prospect and revenue,feasibility of the average income ,tecnicall and economically.